Teaching About Rape in War and Genocide
128 p.
Keywords: This edited volume is both a guide for educators and a resource for everyone who wants to strengthen resistance against a major atrocity that besieges human development. Its contributors explore a crucial question: how to teach about rape in war and genocide?